Al-Mushthalahât Fî Nasyât Al-Khiyâthah Wa Al-Istifâdah Minhâ Fî Tanmiyah Mahârah Al-Kalâm - Musfiroh; Sa’adiyah Ratnasari Sagala (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2020)
يعد علم المصطلح من العلوم المهمة لدى كثير من علماء اللغة. ومن أبرز المصطلحات الشائعة هو المصطلحات في نشاط الخياطة وهو من الأنشطة التي يمارسها الناس كثيرًا. وتلك المصطلحات إن كانت بالعربية يمكن أن تكون وسيلة من وسائل مهارات اللغة العربية. فهدفت هذه الدراسة إلى معرفة المصطلحات في نشاط الخياطة وكيفية الاستفادة منها في تنمية مهارة الكلام. والدراسة هي البحث الكيفي بمنهج الوصف التحليلي، فلتحقيق الهدف سلكت هذه الدراسة طريقة الوثائق والمقابلة. وأما طريقة تحليل البيانات تكون بطريقة مايلس وهامبرمان من جمع البيانات وعرضها ثم الاستنتاج. وقد حصلت الدراسة على نتيجتين هما: 1. توجد مصطلحات نشاط الخياطة في مواقع الشبكة الدولية ولم يوجد كتاب باللغة العربية فيما يتعلق بذلك، فجمعت الباحثة وحصلت على نحو ثلاثة وخمسين مصطلحا من الأدوات المستخدمة فيها، وعمليتها، وخطواتها، وأنواعها وتنوع طرائقها، 2. من خلال وصف مصطلحات نشاط الخياطة وتحليلها تمكن الاستفادة منها في تنمية مهارة الكلام. وذلك بعرض طريقة الاستفادة من المصطلحات باستخدامها في تكوين الجمل المفيدة وموضع الحوار والتدريبات. Terminology is an important science for many linguists. One of the most common terms is the term in the sewing activity, “people practice a lot”. And those terms, if using Arabic, can be a media of Arabic language skills. This study aims to find out the terminology in sewing activities and how to use it in developing speaking skills. The research uses qualitative method an analytic description approach. To reach these aims an objectives, this research follows the method of documents and interviews. The method to analyze data is by collecting, presenting, and withdrawing Miles and Huberman data. The result revealed that two: 1. The provisions of sewing activities are on the international website and there are no books in Arabic about this, and than the researcher collected and obtained about 53 terms of the tools used in that activities, their process, steps, types, and diversity of methods. 2. Description of the terminology and analysis of sewing activities that can be used to develop speaking skills. To showing how to use terminology, use it to form sentences, dialogues, and exercises.